2008
DOI: 10.2337/dc08-1816
|View full text |Cite
|
Sign up to set email alerts
|

Association Among Serum Perfluoroalkyl Chemicals, Glucose Homeostasis, and Metabolic Syndrome in Adolescents and Adults

Abstract: OBJECTIVE -Perfluoroalkyl chemicals (PFCs) have been used worldwide in a variety of consumer products. The effect of PFCs on glucose homeostasis is not known. RESEARCH DESIGN AND METHODS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
168
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(183 citation statements)
references
References 23 publications
10
168
5
Order By: Relevance
“…They also found that there was no difference in PFOS levels between those taking and not taking medication. Sensitivity analyses of those on cholesterol lowering medication did not impact the effect estimates (Château-Degat et al, 2010;Lin et al, 2009;Sakr et al, 2007a, b). In addition, the removal of participants using cholesterol lowering medication may bias the results by removing the diseased participants and leaving those with untreated high cholesterol.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They also found that there was no difference in PFOS levels between those taking and not taking medication. Sensitivity analyses of those on cholesterol lowering medication did not impact the effect estimates (Château-Degat et al, 2010;Lin et al, 2009;Sakr et al, 2007a, b). In addition, the removal of participants using cholesterol lowering medication may bias the results by removing the diseased participants and leaving those with untreated high cholesterol.…”
Section: Discussionmentioning
confidence: 96%
“…Nelson et al (2010) reported that people in the highest PFOA quartile had TC levels 0.36 mmol/L higher than those in the lowest quartile. Lin et al (2009) investigated the relationship between PFAAs and components of metabolic syndrome using NHANES data and found that increased serum PFNA concentrations are associated with a lower prevalence of HDLC below the criteria. Our results for PFNA were consistent with Nelson's study; people in the highest PFNA quartile had ln-TC and ln-LDLC levels 0.25 and 0.33 mmol/L higher than those in the lowest quartile, respectively (Nelson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…First, evidence has shown associations between MetS and selected environmentally hazardous materials, with difference noted in the associations by sex. For example, previous studies reported that serum perfluoroalky chemicals (PFCs), a class of human-made organic chemicals, were associated with glucose homeostasis and indicators of MetS, 29 and several studies have reported the sex-specific toxicity after exposed to PFCs. 30,31 Experimental studies showed that the biological half-life of PFCs in male rats is 70 times longer than in female rats, and the difference is mainly attributed to a difference in renal clearance [CL(R)].…”
Section: Discussionmentioning
confidence: 99%
“…In rats, fasted serum glucose was not affected by 0.5 or 1.5 mg/kg PFOS, although 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 33 insulin and leptin were increased (Lv et al, 2013). In a human study, PFOA and PFOS concentrations were negatively associated with serum glucose levels both in adolescents and adults, but not statistically significant (Lin et al, 2009). However, associations between PFOA or PFOS and various parameters linked to metabolic syndrome were significant.…”
Section: Determination Of Internal Doses Of Pfoa and Pfosmentioning
confidence: 95%